2019
DOI: 10.31083/j.rcm.2019.02.55
|View full text |Cite
|
Sign up to set email alerts
|

Anticoagulation for intra-cardiac thrombi in peripartum cardiomyopathy: A review of the literature

Abstract: Peripartum cardiomyopathy is a type of non-ischemic cardiomyopathy with a high rate of thromboembolic events. Guiding strategies for anticoagulation in patients with peripartum cardiomyopathy and thromboembolic events are limited. Literature for all cases of peripartum cardiomyopathy with intracardiac thrombi were reviewed and summarized from twelve case reports. Based on the available literature, we conclude that patients with peripartum cardiomyopathy with ejection fraction of less than 30% should strongly c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 29 publications
(35 reference statements)
0
7
0
Order By: Relevance
“…Therefore, regular assessments of LVEF should be conducted over a period of 6 to 12 months ( 41 ). Although a full recovery is usually achieved within 2 to 6 months from diagnosis, a potential delay up to 5 years has been reported ( 50 ). A cohort study of 36 patients with PPCM [100% with ejection fraction (EF) <45% and 75% with EF <35%] not on prophylactic anticoagulation, showed that, during the 2-year follow-up period, 5 (14%) thromboembolic complications occurred and 2 patients with stroke died.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, regular assessments of LVEF should be conducted over a period of 6 to 12 months ( 41 ). Although a full recovery is usually achieved within 2 to 6 months from diagnosis, a potential delay up to 5 years has been reported ( 50 ). A cohort study of 36 patients with PPCM [100% with ejection fraction (EF) <45% and 75% with EF <35%] not on prophylactic anticoagulation, showed that, during the 2-year follow-up period, 5 (14%) thromboembolic complications occurred and 2 patients with stroke died.…”
Section: Resultsmentioning
confidence: 99%
“…Finally, bromocriptine, a dopamine agonist that inhibits the release of prolactin, has demonstrated a high rate of full LV recovery in PPCM ( 50 ). Although some case reports suggested that bromocriptine is associated with thromboembolic complications, two prospective cohort studies in ESC and non-ESC countries reported no difference in thromboembolic events with bromocriptine compared [5 events in 84 patients (6%) on bromocriptine vs. 26 events in 463 patients (6%) not on bromocriptine; P=0.802] ( 2 , 28 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A number of PPCM cases presenting with thromboembolism have been reported in the literature. 15 Although most of them are central, pulmonary and peripheral, coronary thromboembolism has been reported in only 4 cases and is one of the most risky and challenging in differential diagnosis among all thromboembolic complications. [8][9][10][11] No clinical studies are available to guide treatment for cases of coronary embolism without underlying coronary disease, but initiation of reperfusion therapy is indicated (standard for myocardial infarction).…”
Section: Discussionmentioning
confidence: 99%
“…3 TEs have been observed in 5-9% of women with PPCM, 3,6 and an LV thrombus has been revealed in up to 10-15% of cases. 7 In 2011, more than 100 national and affiliated member cardiac societies of the European Society of Cardiology (ESC) were invited to contribute to the generation of a global PPCM registry under the auspices of the ESC EURObservational Research Programme (EORP). 8 This registry aims to describe disease presentation, comorbidities, diagnosis, and therapeutic management of women with PPCM.…”
mentioning
confidence: 99%